HUBUNGAN PAPARAN TOLUENE DENGAN GANGGUAN FUNGSI HATI PADA PEKERJA BAGIAN PENGECATAN SEBUAH INDUSTRI KAROSERI DI MAGELANG - Mirror Sabda Mahendra Amien; Ari Suwondo; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2015)
Toluene was a volatile organic compound (VOC) or organic chemicals that very easy to vapor in room temperature. Toluene that fat soluble so easily accumulated in organs that contain lots of fat, one of them was liver. Liver was the main organ in the metabolism of toxic substances including toluene. Toluene metabolism produces reactive oxygen species (ROS) that was free radicals can damage cells. Indicator that used to detect the presence of liver damage was the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in the blood. The purpose of this study was to determine the association between toluene exposure with liver dysfunction in workers painting. This research used analytic observational method with cross-sectional approach. The population of of this study was 26 people. Sampling technique used total sampling. Analysis of association between toluene concentration with levels of ALT and AST, working period with AST used Spearman Rank test, work period with ALT levels used Pearson Product Moment. The results of this current research showed no association between toluene concentration with levels of ALT and AST in the blood, there is a association between work period with ALT levels and there is no association between work period with AST levels in the blood. Advice given that workers should wear a mask a respiratory purifiying when did the painting to reduce the toluene exposure.